Ship-to-shore power information management and design of monitoring system - Shu LIU; Jijun BAI; Sha WAN; Haojing WANG (Dianxin kexue)
The ship shore power system can provide reliable power supply to moored ships and achieve the purpose of energy saving and emission reduction.It is a major advancement in the field of power supply for ports and ships.Taking mobile shore power system as an example,the necessity of using shore power technology for ships was introduced.The function of ship-to-shore power information management and monitoring system was analyzed.The overall framework was divided into four levels and discussed.The basic functions and interrelationships of the layers were analyzed in detail.The architecture and functional modules of the software design were described,and the research and development of the software of each functional module were introduced.